"Hidden invaders" conquer the Sicily Channel and knock on the door of the Western Mediterranean sea. (30th September 2019) - Guastella, Roberta; Marchini, Agnese; Caruso, Antonio; Cosentino, Claudia; Evans, Julian; Weinmann, Anna E.; Langer, Martin R.; Mancin, Nicoletta
Abstract: This study updates the current distribution, range expansion and establishment status of the non-indigenous species Amphistegina lobifera Larsen, 1976 and other foraminifera that are cryptogenic in the Sicily Channel. Prior to this study, amphisteginids were reported from the Levantine Basin, the Central Mediterranean (Tunisia, Malta, Pelagian islands) and the southern Adriatic Sea. Here, we provide new records documenting a north-western expansion in the Central Mediterranean. In summer-autumn 2017 and spring-summer 2018, we collected algae and sediment samples from shallow coastal habitats along the shores of the Maltese archipelago, southern and north-western Sicily, Pantelleria and the Aegadian islands. Analysis of the foraminiferal assemblages showed that A. lobifera is effectively established around Malta and in southern/south-eastern Sicily, and has reached the oceanographic boundary between the Central and Western Mediterranean. Our results also show that the thermotolerant A. lobifera is at an advanced stage of invasion in the Sicily Channel, probably favoured by a recent rise in Mediterranean sea surface temperatures. New species distribution models are provided for the years 2040–2050 and 2090–2100, indicating that the predicted warming trend will facilitate north-westward migration of Mediterranean amphisteginids along the coast of northern Africa into the Alboran Sea, and deep into the Adriatic Sea. Highlights: Amphistegina lobifera has colonized new sites within the Sicily Channel. A. lobifera is effectively established in Malta, Pantelleria and southern Sicily. The invasion of A. lobifera is at an advanced stage in the Sicily Channel. New species distribution models predict remarkable range expansions.